Pluralisme Agama dan Toleransi dalam Pandangan Islamic Worldview - Amirudin, Fajar; Jayyid, Difa’ul Fikri; Muchasin, Fiki Vendi; Sumiran, Sumiran (Lembaga Yasin AlSys, 2025)
Understanding differences, particularly in the context of religious beliefs is not an easy task, as it touches the most fundamental aspects of a person’s value system and identity. It requires an open heart and the awareness that every human being is created in diversity by Allah (SWT). Physical differences may be relatively easier to accept, but when the differences pertain to beliefs and religious teachings, each of which claims absolute truth the potential for conflict increases significantly. Every religion teaches a non-negotiable truth, including Islam. While such absolutism is valid within the theological domain, it can become a source of tension if not accompanied by a wise understanding of diversity. Within the framework of pluralism, understanding differences does not mean equating or blending beliefs, but rather recognizing their existence as part of the divine reality that must be respected. Differences are not to be eliminated but embraced as a strength for building cooperation, reinforcing human solidarity, and achieving a harmonious life. Therefore, tolerance toward religious differences is essential for fostering dignified and civilized human relations.